Strategies for Early Peak Performance Artistic Athletes' Retirement from Sport. (4th March 2022) - Rich, Jason; Pottratz, Suzanne T.; Perreault, Melanie
Abstract: Transitioning out of sport is associated with many changes in an athlete's life that can be distressing and difficult to cope with. As a result, it is not uncommon for athletes to struggle with a variety of issues including a crisis of identity and loss of social support. Since many artistic athletes (e.g., gymnasts, figure skaters) peak at a relatively young age, they also tend to retire at a younger age than other athletes and have developed fewer coping strategies and resources to navigate their way through the changes that come with leaving sport. Recommendations are provided in this article for how coaches can best support and educate their athletes in order to facilitate a positive transition out of sport.